A qualitative study exploring the views of individuals with knee osteoarthritis on the role of physiotherapists in weight management: A complex issue requiring a sophisticated skill set. (1st March 2019) - Allison, Kim; Delany, Clare; Setchell, Jenny; Egerton, Thorlene; Holden, Melanie; Quicke, Jonathan; Bennell, Kim
Abstract: Objectives: The aim of the present study was to explore the attitudes of individuals with knee osteoarthritis (OA) towards the role of physiotherapists in weight management in knee OA. Methods: The study took the form of a qualitative semi‐structured telephone interview study. Participants included 13 purposively sampled individuals with symptomatic knee OA who were overweight or obese by body mass index. Each participated in a semi‐structured telephone interview exploring their perspectives regarding the potential role of physiotherapists in weight management in knee OA. Data were transcribed and analysed using a thematic approach. Results: Three main themes were identified, which highlighted that individuals with knee OA: (a) recognize that weight management is complex; (b) consider that a special skill set is required by clinicians for weight management; and (c) expressed ambivalence towards physiotherapists' role in weight management, with a focus on the role of exercise prescription. Conclusions: Although participants were open to physiotherapists taking on a weight management role within a multidisciplinary team, they were uncertain about whether physiotherapists had the skills and scope of practice needed to address this complex issue. The findings highlight the importance of engagement by physiotherapists in meaningful dialogue with patients, to understand better their experiences, expectations and preferences, and establish if, when and how to integrate patients in weight management discussions in the treatment plan for their knee OA.